2019
DOI: 10.1007/s12035-019-1585-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Proteome Profiling of Neural Induced Pluripotent Stem Cells from Individuals with Down Syndrome Disclose Dynamic Dysregulations of Key Pathways and Cellular Functions

Abstract: Down syndrome (DS) or trisomy 21 (T21) is a leading genetic cause of intellectual disability. To gain insights into dynamics of molecular perturbations during neurogenesis in DS, we established a model using induced pluripotent stem cells (iPSC) with transcriptome profiles comparable to that of normal fetal brain development. When applied on iPSCs with T21, transcriptome and proteome signatures at two stages of differentiation revealed strong temporal dynamics of dysregulated genes, proteins and pathways belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…Herein, we set out to analyze the methylation pattern of all known CpG regions and promoters in trisomic and matched euploid iPSCs differentiated into the neural lineage. The iPSCderived neural model used in this study has shown a transcriptional profile comparable to that of fetal brains at the early and mid-gestational stages, respectively [10]. We present herein the identification of CpGs regions and promoters across the genome with a consistent pattern of differential methylation pattern in T21 neural cells at two distinct stages of differentiation when compared to euploid cells.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Herein, we set out to analyze the methylation pattern of all known CpG regions and promoters in trisomic and matched euploid iPSCs differentiated into the neural lineage. The iPSCderived neural model used in this study has shown a transcriptional profile comparable to that of fetal brains at the early and mid-gestational stages, respectively [10]. We present herein the identification of CpGs regions and promoters across the genome with a consistent pattern of differential methylation pattern in T21 neural cells at two distinct stages of differentiation when compared to euploid cells.…”
Section: Introductionmentioning
confidence: 80%
“…Staining and RNA sequence analysis of neural markers confirmed that the composition of major neural cell types was comparable in trisomic and euploid cultures, and at both differentiation stages (Additional file 1a, b). The transcriptional profiles at the NPC and DiffNPC stages correspond to that of different brain regions, including the hind-and midbrain, at early-and mid-gestation, respectively [10].…”
Section: Neural Ipscs Derivatives With T21 Show Differentially Methylmentioning
confidence: 98%
See 3 more Smart Citations